دور قادة الرأي في عملية اتخاذ القراربالمؤسسة العمومية دراسة ميدانية الإقامة الجامعية مداقين محمد سوق أهراس - بن عثمان فيصل (My University, 2021)
summary: This study aims to know the role of opinion leaders in the decision-making process in the public institution and the level of satisfaction with job performance, by answering the following question: What is the role of opinion leaders in the decisionmaking process of university residence, Madaqin Muhammad? The reason for choosing this topic is due to an attempt to dig deeper to clarify the importance and role of opinion leaders in decision-making within the organization (university residence), and the importance of this study lies in the fact that the progress and development of organizations and their continuity depends mainly on administrative leaders and student organizations that plan and work on Take appropriate decisions and solve crises. ------------------------------------ ملخص: تهدف هذه الدراسة إلى معرفة دور قادة الرأي في عملية صنع القرار في المؤسسة العامة ومستوى الرضا عن الأداء الوظيفي، وذلك من خلال الإجابة على السؤال التالي: ما دور قادة الرأي في عملية صنع القرار بالسكن الجامعي (مداقين محمد)؟ يعود اختيار هذا الموضوع إلى محاولة التعمق في توضيح أهمية ودور قادة الرأي في صنع القرار داخل المؤسسة (السكن الجامعي)، وتكمن أهمية هذه الدراسة في أن تقدم وتطور المنظمات واستمراريتها يعتمدان بشكل أساسي على القيادات الإدارية والمنظمات الطلابية التي تخطط وتعمل على اتخاذ القرارات المناسبة وحل الأزمات.
Keywords: قادة الرأي، صنع القرار، المؤسسة العامة، الرضا عن الأداء الوظيفي